PERBEDAAN KELANCARAN PENGELUARAN ASI IBU NIFAS SETELAH PERAWATAN PAYUDARA - Octora, Atika Asta (JURNAL MEDIA KESEHATAN, 2014)
Breast milk (ASI) is the perfect food for infants and contains all the nutrients necessary for the grow than development of infants, issue in this study is the low coverage of exclusive breast feeding for the city of Bengkulu who have not achieved the national target.The purpose of this study was to determine the effect of the Smooth Implementation of Breast Care Spending on Mother Postpartum breast milk in the Work Area Health Center Sukamerindu 2014. This study used a Quasi-Experimental design using Pre-test and Post test design. The independent variabel was the treatment of breast, while the dependent variabel is the smooth expenditure breast milk. The population was all of 1-7 days postpartum mother. It was 30 people. The sampling technique used is total sampling that (15 treatment group and 15 control group). This study starts from 01 January to12 February 2014 in the Work Area Health Center Sukamerindu. From the research results obtained in the treatment group was average of smoothness ASI output prior to treatment was 4.93 and after breast care is 9.33. In the control group the average of smoothness of spending breastfeeding in the first observation was 4.73 and the second observation is 7.07. Processing data using the t test with α = 0.05 obtained significant value ρ = 0.000 , it means ρ< α or ρ = 0.000 < α = 0.05 means that there is an influence on breast care changes in the smooth of breast milk, from breast milk is not out to be out.